PENGARUH AKTIVITAS DAN PROFITABILITAS YANG MEMPENGARUHI KINERJA KEUANGAN PADA PERUSAHAAN SUB SEKTOR TEKSTIL DAN GARMEN YANG TERDAFTAR DI BURSA EFEK INDONESIA (BEI) PERIODE 2016 - 2021 - Djakariya Djakariya; Solihin Solihin; Yeni Elfiza Abbas; Indra Peedana Singawinata (Sekolah Tinggi Pariwisata Mataram, 2022)
This study aims to analyze the financial performance of the sub-sector and textile and garment companies listed on the Indonesia Stock Exchange (IDX) in 2016-2021 which are assessed using an activity ratio consisting of current asset turn over (CATO), fixed asset turn over (FATO). The profitability ratio consists of gross profit margin (GPM) and operating profit margin (OPM). The activity ratio is a financial ratio that aims to see the effectiveness of the company in using its assets. Profitability ratio is a ratio that describes the company's ability to generate profits. This study uses a descriptive approach, with the type of research data in the form of quantitative data and data sources namely secondary data. The data collection technique used is documentation and the data analysis technique used is descriptive analysis. The results of this study can be concluded that the financial performance of the sub-sector and textile and garment companies listed on the Indonesia Stock Exchange (IDX) in 2016-2021. In order to survive, the company must be in a favorable condition. If the company is in an unfavorable condition, it will be difficult for the company to obtain loans from creditors or investment from outside parties. In this study, the company's performance measurement is measured by profitability ratios and activity ratios, both of which are able to provide high returns on investment so that companies carry out more comprehensive financial statement disclosures to convince investors. The higher the profitability ratio and the activity ratio, the higher the company's ability to earn profits and the better its financial performance. Indirectly this can describe the company's ability to earn profits through all existing capabilities and sources such as sales activities, cash, capital, number of employees, number of branches and so on.